Innovation Policy of European Chemical Companies - Supriyo Das (Publicacions Universitat Rovira i Virgili, 2016)
The European chemical industry is key to economic development and wealth. It creates modern products and materials, and provides virtually all sectors of the economy with technical solutions. The European chemical industry supplies virtually all sectors of the economy and accounts for 17.8% of the total sales of chemicals in the world. It is one of the largest and most R&D-intensive manufacturing sectors in all the advanced economies, and its innovative patterns and productivity growth processes can have profound impacts on economic growth as a whole. In a recent study, Tullo shows that 19 of the top 50 global chemical companies are headquartered in Europe and they make 14.5% of all sales of chemicals in the world. The purpose of this book is to provide an overview of the status of the European chemical industry and the problems it currently faces. According to specialists, innovation and research are key to securing the future of the European chemical industry. Research and development is one way in which companies can ensure future growth by developing new products or processes to improve and expand their operations. The book discusses investment in research and development in the European chemical industry in general and also in the top fifteen European chemical companies in particular. In order to understand research strategy and trends in innovation, we analyze R&D investment, the patent landscape, university-industry collaboration and the regional distribution of chemical companies.